Manajemen Laba dan Efisiensi Investasi: Studi pada Perusahaan Indonesia 2019–2023 - Mutiara Syalwa; Yulia Saftiana; Hendra Susanto (Politeknik Ganesha Medan, 2025)
Investment efficiency is a critical indicator of how well firms allocate capital to value-adding projects. Beyond traditional performance metrics, the credibility of financial reporting shapes investors’ beliefs and, in turn, real investment decisions. This study examines whether earnings management (EM) influences investment efficiency (IE). The sample comprises 315 Indonesia-based firms observed over 2019–2023 drawn from the London Stock Exchange Group (LSEG) database using a purposive sampling method. This is a quantitative study, EM is measured using performance-adjusted discretionary accruals (Kothari et al., 2005), while IE is proxied by the deviation of actual investment from its “normal” level (Biddle et al., 2009). Data analysis includes classical assumption tests, descriptive statistics, multiple linear regression, and hypothesis testing. The results indicate that EM has a negative and significant effect on IE. These findings are consistent with signaling theory, which posits that low-credibility, low-cost signals such as earnings manipulation heighten information asymmetry, weaken the linkage between investment and fundamentals. Practically, firms should strengthen reporting governance and align managerial incentives with long-term performance to curb EM and improve capital allocation. Future research is encouraged to expand the scope to the ASEAN region and incorporate using ownership structure as moderating factors to better explain the EM and IE relationship. This study is limited to the Indonesian context and further research across ASEAN countries is needed to enhance generalizability.